THE ILLOCUTIONARY ACTS OF SECOND SEMESTER STUDENTS IN SPEAKING IN PROFESSIONAL CONTEXT AT UNDIKMA - Ni Wayan Prami Wahyudiantari; Sri Ariani (STKIP PGRI Jombang, 2022)
This research aims to find out the types of illocutionary acts are performed in second semester students (speaking in professional context subject) at UNDIKMA in teaching and learning process. This research applied descriptive qualitative approach. The data collection techniques in this study were the free of charge listening technique and note taking technique. The data analysis technique in this study used the pragmatic equivalent method. Based on the data analysis the conclusion can be drawn is the types of illocutionary acts found are assertive, directive, commissive, and expressive.